INOVASI DAN TANTANGAN DALAM PENDIDIKAN KEPERAWATAN ERA MODERN: TINJAUAN LITERATUR - Umasugi, Muhammad Taufan (Universitas Pesantren Tinggi Darul Ulum, 2025)
Background: Nursing education has undergone significant transformation in the last decade, particularly with the integration of technology and the impact of the COVID-19 pandemic. Objective: To analyse trends in innovation, challenges, and developments in nursing education based on the latest literature. Method: A systematic literature review of 33 articles from various international journals published between 2020 and 2024. Results: Five main themes were identified: (1) integration of technology and simulation, (2) adaptation of post-COVID-19 learning, (3) clinical learning and competencies, (4) diversity and inclusion, and (5) the global context of nursing education. Conclusion: Modern nursing education requires a holistic approach that integrates technology, considers cultural diversity, and adapts evidence-based learning methods to produce competent and character-driven nurses.